Inflammatory optic neuropathy in granulomatosis with polyangiitis can mimick isolated idiopathic optic neuritis. Issue 1 (January 2021) - Clément, Manon; Néel, Antoine; Toulgoat, Frédérique; Weber, Michel; Godmer, Pascal; Hutin, Pascal; Hamidou, Mohamed; Lebranchu, Pierre
Objective: We describe a clinico-radiological presentation of inflammatory optic neuropathy that mimicked optic neuritis. Methods: Retrospective single-center case series and literature review of optic neuropathy without orbital pseudotumor. Results: Five local patients fulfilled the inclusion criteria. Clinical presentation revealed rapidly progressive severe unilateral visual loss, retrobulbar pain (n = 4), and paralytic strabismus (simultaneous = 2, protracted = 2) without proptosis. Optic nerve abnormality was not appreciated on initial scan review. Patients did not have any general activity of the granulomatosis with polyangiitis. Upon follow-up magnetic resonance imaging and initial imaging review, all patients revealed orbital apex anomalies. Visual acuity improved in three patients who received high-dose intravenous glucocorticosteroids immediately. Relapse was frequent and visual outcome was poor (final vision > 20/40 in two patients only). Literature review identified 16 well-documented cases of granulomatosis with polyangiitis–related isolated optic neuropathies. Magnetic resonance imaging revealed no abnormality (n = 6), optic nerve and/or sheath involvement (n = 9), apex infiltration (n = 3), and/or pachymeningitis (n = 7). Conclusion: Granulomatosis with polyangiitis is a rare yet potentially blinding cause of inflammatory optic neuropathy. Optic neuropathy in granulomatosis with polyangiitis may occur in the absence of systemic symptoms of disease activity and is challenging to distinguish from other inflammatory and non-inflammatory disorders affecting visual acuity. Several clinical and imaging clues suggest that optic neuropathy results from the development of an extravascular granulomatous process within the optic nerve sheath in the orbital apex, a place that is difficult to image. In a granulomatosis with polyangiitis patient with unexplained visual loss and a seemingly normal workup (fundoscopy, biology, and imaging), clinician should keep a high index of suspicion.